2021
DOI: 10.1242/dev.199378
|View full text |Cite
|
Sign up to set email alerts
|

KLF17 promotes human naïve pluripotency but is not required for its establishment

Abstract: Current knowledge of the transcriptional regulation of human pluripotency is incomplete, with lack of inter-species conservation observed. Single-cell transcriptomics analysis of human embryos previously enabled us to identify transcription factors, including the zinc-finger protein KLF17, that are enriched in the human epiblast and naïve hESCs. Here we show that KLF17 is expressed coincident with the known pluripotency-associated factors NANOG and SOX2 across human blastocyst development. We investigate the f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 98 publications
0
13
0
Order By: Relevance
“…For example, whereas GATA3 induces TE fate (Ralston et al , 2010; Deglincerti et al , 2016; Gerri et al , 2020a), GATA6 and GATA4 are implicated in primitive endoderm specification and maintenance (Chazaud et al , 2006; Plusa et al , 2008; Roode et al , 2012). Among KLFs, which generally play roles in pluripotency maintenance, KLF2 marks murine epiblast but is absent in humans, whereas KLF17 is widespread in human blastocysts but absent in mouse (Yeo et al , 2014; Blakeley et al , 2015; Lea et al , 2021). Enrichment of KLF motifs in bovine morula, ICM, and TE is reminiscent of the widespread expression of KLF17 in human embryos, but it remains to be determined which member(s) of the KLF family are active in bovine; several candidates are expressed at the blastocyst stage, including KLF6 , which undergoes a 14‐fold increase in expression between the 16‐cell and blastocyst stages (Fig EV5B).…”
Section: Resultsmentioning
confidence: 99%
“…For example, whereas GATA3 induces TE fate (Ralston et al , 2010; Deglincerti et al , 2016; Gerri et al , 2020a), GATA6 and GATA4 are implicated in primitive endoderm specification and maintenance (Chazaud et al , 2006; Plusa et al , 2008; Roode et al , 2012). Among KLFs, which generally play roles in pluripotency maintenance, KLF2 marks murine epiblast but is absent in humans, whereas KLF17 is widespread in human blastocysts but absent in mouse (Yeo et al , 2014; Blakeley et al , 2015; Lea et al , 2021). Enrichment of KLF motifs in bovine morula, ICM, and TE is reminiscent of the widespread expression of KLF17 in human embryos, but it remains to be determined which member(s) of the KLF family are active in bovine; several candidates are expressed at the blastocyst stage, including KLF6 , which undergoes a 14‐fold increase in expression between the 16‐cell and blastocyst stages (Fig EV5B).…”
Section: Resultsmentioning
confidence: 99%
“…For example, whereas GATA3 induces TE fate 59,62,63 , GATA6 and GATA4 are implicated in primitive endoderm specification and maintenance [64][65][66] . Among KLFs, which generally play roles in pluripotency maintenance, KLF2 marks murine epiblast but is absent in humans , whereas KLF17 is widespread in human blastocysts but absent in mouse [67][68][69] . The enrichment of KLF motifs in bovine morula, ICM, and TE is reminiscent of the widespread expression KLF17 in human embryos, but it remains to be determined which member(s) of the KLF family are active in bovine; several candidates are expressed at the blastocyst stage, including KLF6, which undergoes a 14-fold increase in expression between the 16-cell and blastocyst stages (Extended Fig.…”
Section: Chromatin Accessibility Precedes Establishment Of Canonical ...mentioning
confidence: 99%
“…By engineering cells that expressed gene-specific CRISPR-interference to transcriptionally repress NANOGP1 , we found that naïve hPSCs were unaffected by the robust knockdown of NANOGP1 . Interestingly, the capacity of NANOGP1 to induce naïve pluripotency but be unnecessary for its maintenance parallels another naïve pluripotency factor – KLF17 ( Lea et al, 2021 ). In contrast, the knockdown of NANOG caused naïve hPSCs to exit the naïve state and differentiate towards the trophoblast lineage.…”
Section: Discussionmentioning
confidence: 99%